BURNOUT SYNDROME IN MILITARY POLICE OFFICERS: AN INVESTIGATION IN THE 3º MILITARY POLICE BATTALION IN PATOS-PB (REMUNOM, 2025)
AbstractIntroduction: Military police activity presents work factors that can physically and emotionally overload professionals, affecting their quality of life and health. Stress at work can result in health problems, including Burnout Syndrome (BS). Objective: To analyze the prevalence of Burnout Syndrome in military police officers (PMs). Method: The study adopted a descriptive-exploratory field research, with a quantitative approach, involving military police officers of the 3ºBPM – PMPB, stationed in Patos-PB. Data were collected using questionnaires, including the Maslach Burnout Inventory (MBI) and one created by the author, answered by participants who signed the Informed Consent Form (ICF). The inclusion criteria were PMs assigned to the 3ºBPM, of both sexes, working in administrative and/or operational environments. Inactive PMs and those who refused to take part were excluded. The study was approved by the Research Ethics Committee under nº 7.223.144. Results: The average age of the participants was 42 years old, predominantly men working in the operational sector. It was observed that 63% of them felt overworked and 71% felt undervalued, especially in financial terms. The latter factors are closely related to the presence of signs and symptoms of BS. In addition, 23% of the participants had a moderate classification for Burnout Syndrome. Of the variables, 23% had moderate Emotional Exhaustion, 27% were classified with high depersonalization, and Professional Achievement had the lowest index (67%), indicating greater wear and tear. Conclusion: considerable rates of BS were observed in the police officers investigated.Keywords: Burnout; Stress; Police.